Assistance in managing household investments and finances with Android-based applications - Yunisvita Yunisvita; Sri Andaiyani; Muhammad Komri Yusuf (University of Merdeka Malang, 2022)
Family financial management serves to control fluctuations in the family or personal income and expenses. The use of Android-based applications supports financial management to be easier and more practical. Community service activities carried out by the implementation team from the Faculty of Economics, Sriwijaya University aims to provide knowledge in managing household investments and finances with an Android-based application. This program is based on concerns about the lack of knowledge around family financial optimization, especially in the process of recording a nominal amount of exit and entry within a certain period of time. Thus, problems and opportunities can be detected that can even be used as an investment and increase the available fund reserves. The participants consisted of 36 teachers of Junior/Senior High School (SMP/SMA) Dharma Bakti Palembang. The method of implementation is carried out by presentations, tutorials, discussions, and evaluations. Participants are already aware of the steps in using financial applications and investing in their Androids. Participants can also make investments and have income from the investments they make. This activity has a positive impact on increasing the knowledge and skills of participants in managing finances and managing investments, thereby increasing the number of hopes to improve family welfare in the future.